Essentials of nucleosynthesis and theoretical nuclear astrophysics - Rauscher, Thomas, 1964- (IOP (Series). Release 6., 2020)
Studies in nucleosynthesis and nuclear astrophysics are highly interdisciplinary, encompassing such fields as nuclear physics, stellar structure and evolution, hydrostatics and hydrodynamics, differential equations for following isotopic abundance changes in stellar plasmas and in the interstellar medium, and astronomical observations. Essentials of Nucleosynthesis and Theoretical Nuclear Astrophysics brings together the theoretical aspects of these topics in a single volume, providing the necessary mathematical tools and equations with unified notation to enable studying nucleosynthesis in a variety of astrophysical sites. Essential definitions and theory are presented that will enable the reader to enter the research field with the familiarity of the specialities and specific problems. Useful as a reference work for any researcher in the field of nucleosynthesis and nuclear astrophysics, or a suitable basis for a graduate course on these topics, the book also provides the information necessary to follow discussions of current open questions in the understanding of the origin of the elements.